2006
DOI: 10.1016/j.seizure.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the multidrug resistance 1 gene in Korean epileptics

Abstract: In Korean epileptics, there was no significant relationship between three known SNPs in MDR1 and drug resistance. And there was no association of MDR1 haplotype based on above three sites with pharmacoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 24 publications
5
40
3
Order By: Relevance
“…[6][7][8] However, most candidate gene association studies on AED resistance have focused on an individual genetic variant with the potential main effect, and none of these studies could find evidence for a strong, single-gene effect on AED resistance. [9][10][11][12] This is partially because of the limitations of parametric statistical methods for detecting gene effects that are solely or partially dependent on interactions with other genes. 13,14 In this study, with the working hypothesis that AED resistance is a polygenic disorder in which several genetic variants with a modest effect interact with each other, we tried to find pharmacogenetic evidence of epistatic interactions underlying AED resistance using a new statistical method.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, most candidate gene association studies on AED resistance have focused on an individual genetic variant with the potential main effect, and none of these studies could find evidence for a strong, single-gene effect on AED resistance. [9][10][11][12] This is partially because of the limitations of parametric statistical methods for detecting gene effects that are solely or partially dependent on interactions with other genes. 13,14 In this study, with the working hypothesis that AED resistance is a polygenic disorder in which several genetic variants with a modest effect interact with each other, we tried to find pharmacogenetic evidence of epistatic interactions underlying AED resistance using a new statistical method.…”
Section: Introductionmentioning
confidence: 99%
“…A further smaller study using a similar outcome definition as used by Siddiqui et al 81 and Tan et al, 82 could not demonstrate an association of outcome with 3435C4T, 2977 G4T, 1236C4T or three SNP haplotype in 108 drugresponsive and 99 drug-resistant Korean patients with epilepsy. 85 In contrast, another study 86 genotyped 10 polymorphisms in 108 drug-resistant and 223 drug-responsive ethnically similar patients. The definition of drug resistance was at least 10 seizures over the preceding year with trials of two to three appropriate anti-epileptic drugs, whereas drug responsiveness was defined as complete freedom from seizures for at least 2 years in patients on any antiepileptic medication.…”
mentioning
confidence: 99%
“…It has previously been reported that most of the analytical methods were specific for the parent drug, although some discrepancies in the results were obtained between high-performance liquid chromatography and fluorescence polarization immunoassays (FPIA). This overestimation might reflect cross-reactivity with CsA metabolites, even when monoclonal antibodies are used in the immunoassays [8,11,28] . In the present study, the co-administration of diltiazem affected the correlation between MDR1 genetic polymorphisms and CsA blood concentrations, likely reflecting the reaction of FPIA with CsA and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 50 single nucleotide polymorphisms (SNPs) have been identified in MDR1, including C1236T, G2677T/A and C3435T in exons 12, 21 and 26, respectively, and these functionally important mutations can form different haplotypes. Both SNPs and haplotypes have been demonstrated as highly polymorphic among individuals and different ethnic groups [6][7][8] . The genetic polymorphisms of MDR1 have been implicated as one of the factors resulting in CsA pharmacokinetic variation.…”
Section: Introductionmentioning
confidence: 99%